Capsaicin ameliorate pulmonary fibrosis via antioxidant Nrf-2/ PPAR- γ pathway activation and inflammatory TGF-β1/ NF-κB/COX II pathway inhibition - Abdulaal, Wesam H.; Asfour, Hani Z.; Helmi, Nawal; Al Sadoun, Hadeel; Eldakhakhny, Basmah; Alhakamy, Nabil A.; Alqarni, Hani Mohammed; Alzahrani, Saeed Ali Mohammed; El-Moselhy, Mohamed A.; Sharkawi, Sara S.; Aboubakr, Esam Mohamed (Frontiers in Pharmacology, 2024)
Bleomycin is an effective antibiotic with a significant anticancer properties, but its use is limited due to its potential to inducecause dose-dependent pulmonary fibrosis. Therefore, this study aimed to assess the therapeutic potential of Capsaicin as an additional treatment to enhance patient tolerance to Bleomycin compared to the antifibrotic drug Pirfenidone. Pulmonary fibrosis was induced in rats through by a single intratracheal Bleomycin administration in day zero, followed by either Capsaicin or Pirfenidone treatment for 7 days. After the animals were sacrificed, their lLlungs were dissected and examined using various stains for macroscopic and histopathological evaluation. Additionally, the study assessed various antioxidant, anti-inflammatory, and antifibrotic parameters were assessed. The animalsRats exposed to Bleomycin exhibited visible signs of fibrosis, histopathological alterations, increased collagen deposition, and elevated mucin content. Bleomycin also led to heightened increased inflammatory cells infiltration in the bronchoalveolar lavage, elevated fibrosis biomarkers such as hydroxyproline, alpha-smooth muscle actin (α-SMA) and transforming growth factor-beta (TGF-β1), increased inflammatory markers including tumor necrosis factor-alpha (TNF-α), interlukine-6 (Il-6), interlukine-1β (Il-1β) nuclear factor-kappa B (NF-κB), and Cyclooxygenase-2 (COX-2), and transforming growth factor-beta (TGF-β1),. Furthermore, it reduced the expression of peroxisome proliferator-activated receptor-gamma (PPAR-γ), increased oxidative stress biomarkers like nitric oxide (NO), malondialdehyde (MDA), myeloperoxidase (MPO) and protein carbonyl. Bleomycin also decreased the expression of nuclear factor erythroid 2–related factor 2 (Nrf-2), reduced glutathione (GSH), total antioxidant capacity, and the activities of catalase and superoxide dismutase (SOD).Treating the animals with Capsaicin and Pirfenidone following Bleomycin exposure resulted in improved lung macroscopic and microscopic characteristics, reduced collagen deposition (collagen I and collagen III) and mucin content, decreased inflammatory cell infiltration, lowered levels of hydroxyproline, α-SMA, and TGF-β1, decreased TNF-α, Il-6, Il-1β, NF-κB, and COX-2, increased PPAR-γ and Nrf-2 expression, and improvement improved in all oxidative stress biomarkers. In summary, Capsaicin demonstrates significant antifibrotic activity against Bleomycin-induced lung injury that may be attributed, at least in part, to the antioxidant and anti-inflammatory activities of Capsaicin mediated by upregulation of PPAR-γ and Nrf-2 expression and decreasing. TGF-β1, NF-κB and COX II proteins concentrations.